Analysis of gene content in sweet potato chlorotic stunt virus RNA1 reveals the presence of the p22 RNA silencing suppressor in only a few isolates: Implications for viral evolution and synergism - Cuéllar, Wilmer Jose; Tairo, F.; Kreuze, Jan F.; Valkonen, J.P.T. (Microbiology Society, 2008)
Sweet potato chlorotic stunt virus (genus Crinivirus) belongs to the family Closteroviridae, members of which have a conserved overall genomic organization but are variable in gene content. In the bipartite criniviruses, heterogeneity is pronounced in the 3'-proximal region of RNA1, which in sweet potato chlorotic stuat virus (SPCSV) encodes two novel proteins, RNase3 (RNase III endonuclease) and p22 (RNA silencing suppressor). This study showed that two ugandan SPCSV isolates contained the p22 gene, in contrast to three isolates of the east african strain from Tanzania and Peru and an isolate of the west african strain from Israel, which were missing a 767 nt fragment of RNA1 that included the p22 gene. Regardless of the presence of p22, all tested SPCSV isolates acted synergistically with potyvirus sweet potato feathery mottle virus (SPFMV; genus Potyvirus, family Potyviridae) in co-infected sweetpotato plants (Ipomoea batatas), which greatly enhanced SPFMV titres and caused severe sweetpotato virus disease (SPVD). Therefore, the results indicate that any efforts to engineer pathogen-derived RNA silencing-based resistance to SPCSV and SPVD in sweetpotato should not rely on p22 as the transgene. The data from this study demonstrate that isolates of this virus species can vary in the genes encoding RNA silencing suppressor proteins. This study also provides the first example of intraspecific variability in gene content of the family Closteroviridae and may be a new example of the recombination-mediated gene gain that is characteristic of virus evolution in this virus family.